A escrita comovida de João Anzanello Carrascoza - Miguel Conde (Estudos de Literatura Brasileira Contemporânea)
The impassible narration, which, in its indifference, emulates the brutality of the episodesit describes, is an essential feature of the most noted Brazilian fictions of the 1990s. The attention devoted to this mimetic realism, whichrelies on shock as the best strategy for anun mediated apprehension of the real, creates a context in which commotion is perceived as naive or suspicious. The reception to the short stories of João Anzanello Carrascoza, which have been described as borderline between sublime and kitsch, exemplifies that. A carefulr eading of his stories, however, shows that in them commotion derives not from a denial of reality,but instead from the recognitionof that which, in the real,is truly inevitable and "idiot", as formulated by Clément Rosset.